2023
DOI: 10.1097/md.0000000000034503
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster virus infection and the risk of developing dementia: A systematic review and meta-analysis

Rowan H. Elhalag,
Karam R. Motawea,
Nesreen Elsayed Talat
et al.

Abstract: Background: Herpes Zoster, commonly known as shingles, is a viral infection that affects a significant portion of the adult population; however, its potential role in the onset or progression of neurodegenerative disorders like dementia remains unclear. Methods: We searched the following databases: PubMed, Scopus, Cochrane library, and Web of Science. We included any randomized control trials and controlled observational studies as Cross-sectional, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
(127 reference statements)
0
8
2
Order By: Relevance
“…This systematic review and meta‐analysis included six studies. Three studies 18 , 19 , 24 were deemed low risk of bias, while three 20 , 25 , 26 exhibited a moderate overall risk. Figure 2 presents the results of the risk of bias assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review and meta‐analysis included six studies. Three studies 18 , 19 , 24 were deemed low risk of bias, while three 20 , 25 , 26 exhibited a moderate overall risk. Figure 2 presents the results of the risk of bias assessment.…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 17 A meta‐analysis focused on non‐randomized observational studies determined no significant relationship between HZ and dementia. 18 HZ can lead to cerebral vasculopathy and stroke, particularly if the cranial nerves are affected, resulting in neurologic damage. 13 Previous studies found that the incidence of stroke and vasculopathy was higher in patients with herpes zoster ophthalmicus (HZO) than in other types of HZ.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, antiviral treatment is linked to a diminished long-term risk of dementia in individuals displaying evident signs of herpes infection. Conversely, a meta-analysis comprising nine studies found no significant association between herpes zoster and the incidence of dementia or Alzheimer’s disease [ 64 ]. However, it did reveal a noteworthy association between herpes zoster opthalmicus and the incidence of dementia [ 64 , 65 ].…”
Section: Postherpetic Complicationsmentioning
confidence: 99%
“…Conversely, a meta-analysis comprising nine studies found no significant association between herpes zoster and the incidence of dementia or Alzheimer’s disease [ 64 ]. However, it did reveal a noteworthy association between herpes zoster opthalmicus and the incidence of dementia [ 64 , 65 ].…”
Section: Postherpetic Complicationsmentioning
confidence: 99%
“…As shown in Figure 1 above, there are several other viruses, including human herpesvirus-6 (HHV-6), -7 (HHV-7) [ 43 , 128 , 129 , 130 , 131 , 132 ], Epstein–Barr virus (EBV) [ 133 , 134 , 135 , 136 , 137 , 138 , 139 ], cytomegalovirus (CMV) [ 33 , 140 , 141 , 142 , 143 ], varicella zoster virus (VZV) [ 144 , 145 , 146 , 147 ], human immunodeficiency virus [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ], hepatitis C virus (HCV) [ 163 ], enterovirus [ 164 , 165 , 166 ], influenza A virus (IAV) [ 167 , 168 , 169 , 170 , 171 ], and measles [ 172 , 173 , 174 , 175 ], which have ...…”
Section: Other Viruses Implicated In Admentioning
confidence: 99%